(untitled) (Observatorio Económico, 2008)
For the past couple of decades, social housing policies in Chile have served to solve the housing deficit problem. But the victory over this housing shortage brought new problems with it: the so-called “spatial concentration of poverty” or, more simply, the existence of cities that are more segregated than homogeneous, cities that concentrated the poor in certain places. This issue of Observatorio Económico, published by the Faculty of Economics and Business (FEN) at Universidad Alberto Hurtado, sheds light on the effects of residential segregation in Chile and finds, among other things, that these effects bear mainly on the development of children and young people living in poor households—and poor places. Continue reading...